Altered tactile localization and spatiotemporal integration in complex regional pain syndrome patients - Trojan, Jörg; Kleinböhl, Dieter; Benrath, Justus; Flor, Herta (European journal of pain, 2018)
Background In complex regional pain syndrome (CRPS), altered perception of the affected hand and neglect-like symptoms of the affected body side are common features. In this study, we presented tactile stimuli to the affected hands in CRPS patients and matched healthy controls. Methods The participants’ task was to point at the perceived positions of the stimuli using a tracking device. The spatial coordinates of the perceived positions were analysed for accuracy and consistency. We also presented patterns consisting of two stimuli at distinct positions with a delay of 100 ms. These patterns are known to induce spatiotemporal integration (“sensory saltation”). Results CRPS patients were less accurate and less consistent in the spatial perception of tactile stimuli on their hands. Furthermore, they showed increased spatiotemporal integration, although these effects were smaller than expected. These deficiencies were related to the clinically assessed intensity of recurrent pain episodes. Surprisingly, the intensity of clinically assessed ongoing pain was associated with increased precision. Conclusions In line with earlier reports, our findings indicate that the representation of the affected hands in CRPS patients is less accurate than in healthy people, probably reflecting reorganization in somatosensory cortices. The exact relationships between these findings and other aspects of CRPS remain to be elucidated. Significance CRPS patients performed poorly in localizing positions on their affected hands via pointing and exhibited increased spatiotemporal integration. The presented method may prove useful in diagnostics as well as psychophysical and neurofunctional research on CRPS and other chronic pain disorders.